2020
DOI: 10.1007/s00199-020-01260-6
|View full text |Cite
|
Sign up to set email alerts
|

Subgame perfection in recursive perfect information games

Abstract: We consider sequential multi-player games with perfect information and with deterministic transitions. The players receive a reward upon termination of the game, which depends on the state where the game was terminated. If the game does not terminate, then the rewards of the players are equal to zero. We prove that, for every game in this class, a subgame perfect ε-equilibrium exists, for all ε > 0. The proof is constructive and suggests a finite algorithm to calculate such an equilibrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…While two-player zero-sum Blackwell games and Blackwell games with perfect information are quite well understood (see, e.g., Martin [34,35], Mertens [38], Kuipers, Flesch, Schoenmakers, and Vrieze [25]), general multiplayer nonzero-sum Blackwell games have so far received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…While two-player zero-sum Blackwell games and Blackwell games with perfect information are quite well understood (see, e.g., Martin [34,35], Mertens [38], Kuipers, Flesch, Schoenmakers, and Vrieze [25]), general multiplayer nonzero-sum Blackwell games have so far received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…A general result for stochastic games with three or more players is lacking thus far. Flesch et al (2010) have demonstrated the existence of a subgame-perfect ε-equilibrium for every ε > 0 for the subclass of recursive stochastic games with non-negative utilities, whereas Kuipers et al (2021) obtain such a result for the subclass of recursive stochastic games with deterministic transitions.…”
Section: Introductionmentioning
confidence: 99%